Dispersi Qt dan T-Wave Alternans pada Elektrokardiogram dengan repolarisasi Dini - Reza Octavianus; Yoga Yuniadi; Budhi Setianto (Jurnal Kardiologi Indonesia, 2012)
Background. It has been well known that early repolarization is only normal ECG variant without significant clinical consequences. However, recent studies show variable results of its relation to ventricular arrhythmias occurence. This study is aimed to seek corellation between early repolarization with more established ventricular arrhythmia marker.Methods. Corellation of early repolarization with QT dispersion and T wave alternans (TWA) in comparation with normal ECG pattern was conducted in a cross secional study. QT interval was measured using tangential methods. QT dispersion is defined as difference of longest and shortest QT interval in 12-lead ECG. TWA is determined by means of time domain modified moving average (MMA).Results. Twenty six subjects with early repolarization and 36 subjects with normal ECG participated in this study. Median age was 30 (20-49) years. Maximum TWA are 29. 5 (9 – 81) vs. 27 (5–81) (p= 0.493), and QT dispersion 20.4 (2.8–47.2) vs. 13.2 (2.4–46.0) ms (p=0.053) in early repolarization and normal ECG group respectively.Conclusion. No significant different of QT dispersion and TWA between subjects with early repolarization as compare to that with normal ECG.